The Word Of 'Basar' And Its Meronym In Quran: Comparative Study Between Quranic Dictionaries - Mohammed Akhiruddin Ibrahim; Hishomudin Ahmad; Robiatul Adawiyah Mohd @ Amat; Muhammad Widus Sempo; Nur Farhana Baharuddin (INT Organization Center Acad Research, 2024)
Non-Indexed Publication